(untitled) (Journal of Chittagong Medical College Teachers’ Association, 2016)
Placenta is a vital organ for maintaining pregnancy and promoting normal foetal development. It is sometimes described as the mirror of the perinatal period. Still one of the common methods of investigation of the factors endangering the foetus and newborn during the perinatal period is the examination of placenta. The present study was conducted to make a gross morphological and histological evaluation of placenta in bangladeshi population. This cross-sectional study was carried out in the department of anatomy, chittagong medical college hospital over a period of 1 year from july 2011 to june 2012. The placentae from mature children delivered through caesarean section between 37 to 40th weeks of gestation with no complications having a birth weight of more than 2.5 kg were the study population. A total of 100 such placentae were consecutively selected from the study population. The morphological study of placenta included placental volume, weight, number of cotyledons, shape, diameter, thickness, mode of insertion of umbilical cord and histological study was volume (%) of villous area of the placenta. The mean age of the mothers whose placentae were studied was 25.3 3.8 years (range: 18 36). The mean birth weight of the neonates was 3.0 0.3 kg. Majority (96%) of the placenta was rounded in shape. The mean weight and volume of the placenta was 538.538.7 g and 45141.03 ml respectively, while the mean diameter was 16.8 + 0.99 cm. The mean thickness was 17.53 3.66 mm. Over 70% of the cords were inserted at the peripheral part of the placenta. The mean number of cotyledons was 18 and the volume of villous area was 51.1%. Majority of the placentae in bangladeshi population is round with the eccentric insertion of umbilical cord. The other features like weight, diameter and thickness, the number of cotyledons and volume of villous area are almost comparable with those of a typical one. JCMCTA 2015 ; 26 (2) : 3 - 8